Asymmetric cointegration relationship between real exchange rate and trade variables: the case of Malaysia - Duasa, Jarita (-, 2009)
The present study attempts to analyze the long-run equilibrium relationship between real exchange rate and trade balance, imports and exports demand by cointegration tests assuming asymmetric adjustment. Following Enders and Siklos (2001), the Engle-Granger two-step cointegration test is expanding to incorporate an asymmetric error correction term. It is found that there exists asymmetric cointegration between balance of trade and real exchange rate when momentum-threshold autoregressive (M-TAR) model is conducted and the study also found asymmetric cointegration between export volume and real exchange rate under threshold autoregressive (TAR) model. From estimation of M-TAR error-correction trade balance model, the adjustment back to equilibrium is more rapid following relative increase in trade balance (above long-run value) compared to relative decrease in trade balance (below long-run value). From TAR error-correction import demand model, the model suggests quick adjustment of import demand once it is below long-run value. The results reflect the evidence of persistence of trade balance deficit in the case of Malaysia which probably due to policies to defend an overvalued exchange rate by protectionist trade policies or capital controls. In addition, the shock of exchange rate on import demand is likely to be temporary in nature.